Menduga Modulus Geser dengan Memanfaatkan Modulus Elastisitas Contoh Uji Ukuran Pemakaian dan Bebas Cacat Predicting Shear Modulus Using the Elasticity Modulus of Full-Scale and Small-Clear Wood Specimen - Indah Sulistyawati; Abdul Muhar Husin; Surjono Surjokusumo (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
To predict the elasticity modulus of wood, an assumption is made that all of deflection is due to the bending moment. Actually the total deflection of a beam made up of a bending and shear component. The composition of the bending deflection has EI as the bending stiffness factor and for the shear deflection has a GA as the shear stiffness factor, where E is the elasticity modulus, I is the moment of inertia, G is the shear modulus and A is the cross sectional area of a beam. The shear modulus of wood can be determined by using the true elasticity modulus of full-scale specimen test and the apparent elasticity modulus of small-clear specimen test of the beam with single load at mid-point for simply supported beam. From the comparison of them the shear modulus of wood can be obtained. The result of this research shown that the shear modulus of Acacia mangium is 1/17.45 multiplies by the elasticity modulus.